PENGEMBANGAN MEDIA PEMBELAJARAN LUDO MATERI FPB DAN KPK PADA SISWA KELAS IV SEKOLAH DASAR - Normaya, Sinta Dwi; Mukmin, Bagus Amirul (Jurnal Pendidikan Dasar, 2024)
Abstract: In the process of learning mathematics on FPB and KPK material, students experience difficulties and cannot understand the material optimally. This is because the teacher does not interesting learning media, only uses image media which makes students less interested. The development objective of this research is to determine the very validity, very effective and very practicality of LUDO media development of FPB and KPK material. The method use is Research and Development (R&D) with the ADDIE model. The results of this study are LUDO learning media FPB and KPK material that has been developed is declared valid, effective, and practical. The average validity results obtained from media experts and material experts were 89,5%, which was categorized as very valid. The effectiveness results obtained during limited trial were 90% and during extensive trials it was 87.5%. The practicality results obtained from teacher response were an average of 98.18%, student responses during the limited trial were 92% and during extensive trials they were 90.31%.